1998
DOI: 10.1021/ic9800785
|View full text |Cite
|
Sign up to set email alerts
|

Vinylic C−H Bond Activation and Hydrogenation Reactions of Tp‘Ir(C2H4)(L) Complexes

Abstract: The substitution of one of the ethylene ligands of the complexes Tp'Ir(C(2)H(4))(2) (Tp' = Tp(Me)()2, 1; Tp' = Tp, 1) by soft donors such as tertiary phosphines or carbon monoxide is a facile reaction that gives the corresponding Tp'Ir(C(2)H(4))(L) adducts. Spectroscopic studies support their formulation as five-coordinate, 18-electron species that possess a distorted trigonal bipyramidal geometry. This proposal has been confirmed by a single-crystal X-ray study carried out with the PMe(2)Ph complex Tp(Me)()2I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
38
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 43 publications
8
38
0
Order By: Relevance
“…Furthermore, if the activation barrier of a S i-H bond is comparably small, the apparent rate determining step would be the dissociative rearrangement from D to B. Our measured rates for the formation of B are also consistent with the observation that the overall enthalpy of activation is dominated by the enthalpy of dissociating the solvent from the reaction site, and that the transition state consists of a very loosely bound R3SiH [90,100].…”
Section: Resultssupporting
confidence: 81%
“…Furthermore, if the activation barrier of a S i-H bond is comparably small, the apparent rate determining step would be the dissociative rearrangement from D to B. Our measured rates for the formation of B are also consistent with the observation that the overall enthalpy of activation is dominated by the enthalpy of dissociating the solvent from the reaction site, and that the transition state consists of a very loosely bound R3SiH [90,100].…”
Section: Resultssupporting
confidence: 81%
“…By forcing the conditions of the reaction (2 atm, 90 °C, 6 h), complex 1* was obtained as the main product in very high yield. Other Ir(III) species can be used as starting materials for the synthesis of 1* , and thus, for example, Tp Me2 IrH(C 2 H 3 )(C 2 H 4 ) , and Tp Me2 Ir(C 6 H 5 ) 2 (N 2 ) react with H 2 at 70−90 °C with ultimate formation of 1* . While in the first case the known 14 Tp Me2 IrH 2 (C 2 H 4 ) can be detected as an active intermediate, in the hydrogenation of the bis(phenyl) derivative no intermediates are observed (NMR monitoring).…”
Section: Resultsmentioning
confidence: 99%
“…The simplest preparative route, and the only one described in the Experimental Section, however, involves the Ir(I) complex Tp Me2 Ir(C 2 H 4 ) 2 9 as the starting material, thus avoiding the preparation of the above-mentioned Ir(III) species that, after all, need be synthesized from the same bis(ethylene) derivative. In that case, the intermediates Tp Me2 IrH 2 (C 2 H 4 ) and Tp Me2 Ir(C 2 H 5 )(C 2 H 4 ) are formed under H 2 , even at room temperature, and further hydrogenation under more forcing conditions (C 6 H 12 , 2 atm, 90 °C, 3 days) is needed to transform this mixture into 1* (eq 1). Quite recently, Venanzi et al have also observed the formation of 1* in the hydrogenation of other Tp Me2 Ir substrates…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] The other mechanistic way [path (b)] was invoked to explain the reactions of Ir-dienes 1-3 with hard Lewis bases (NCMe, pyridine, etc.). The two different mechanisms shown in Scheme 4 may also account for the different types of processes in which the 2,3-dimethylbutadiene derivative 3 (the most reactive among 1-3, and hence the most studied) takes part.…”
Section: Me2mentioning
confidence: 99%